2010
DOI: 10.1055/s-0029-1240709
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pulsatile and Non-pulsatile Left Ventricular Assist Devices on the Renin-Angiotensin System in Patients with End-Stage Heart Failure

Abstract: Our data suggest that pulsatile as well as non-pulsatile left ventricular assist devices are equally able to treat chronic heart failure. However pulsatile devices seem to have a greater impact on reversing the changes in plasma renin activity and might thus offer a greater advantage when recovery of left ventricular function is expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 15 publications
0
36
0
Order By: Relevance
“…Of greater concern is the possibility that this decline in eGFR represents an adverse renal effect of nonpulsatile blood flow (47). Welp et al compared the effect of pulsatile-and continuousflow LVADs on the RAAS in heart failure patients (48). As expected preimplantation, peripheral renin activity and plasma aldosterone concentrations were elevated in both LVAD groups.…”
Section: Continuous Blood Flow and Renal Functionmentioning
confidence: 90%
See 1 more Smart Citation
“…Of greater concern is the possibility that this decline in eGFR represents an adverse renal effect of nonpulsatile blood flow (47). Welp et al compared the effect of pulsatile-and continuousflow LVADs on the RAAS in heart failure patients (48). As expected preimplantation, peripheral renin activity and plasma aldosterone concentrations were elevated in both LVAD groups.…”
Section: Continuous Blood Flow and Renal Functionmentioning
confidence: 90%
“…These findings could be explained by improvements in elevated right heart and renal vein pressures, which increase interstitial pressures that in turn decrease cross-sectional area of intrarenal vessels and diastolic flow. Improvements in renal function by LVADs appears to be mediated by several factors, including reductions in vascular resistance within the kidney from changes in renal venous pressure, RAAS, and sympathetic activity, as well as improvements in cardiac output (48,(71)(72)(73).…”
Section: Improvement Of Rd After Lvad Placementmentioning
confidence: 99%
“…The effect of LVAD therapy on kidney function and physiology has been studied recently with conflicting results and without a clear pathophysiological understanding [11,12,13,14,15,16,17,18,19]. One current limitation to studying this pathophysiology is that LVAD implantation trends have changed from historically pulsatile to exclusively continuous flow device types.…”
Section: What Effect Does Lvad Physiology Have On Kidney Function?mentioning
confidence: 99%
“…Historical physiological studies in patients who received PF-LVAD therapy have demonstrated improved systemic perfusion [20] and decreased levels of renin, aldosterone, and vasopressin [21]. Welp et al [12] demonstrated that the renin levels improved in PF-LVAD and CF-LVAD patient groups, but the improvement was more marked in the PF-LVAD group. Initial clinical studies focused on the effect of LVADs on kidney function over the first 3-12 months after device implantation.…”
Section: What Effect Does Lvad Physiology Have On Kidney Function?mentioning
confidence: 99%
“…19 Although we did not measure renal-adrenal hormones in this study, 1 recent report showed that both plasma renin activity and aldosterone were much greater in patients with nonpulsatile than pulsatile LVADs. 20 The greater plasma renin activity leads to a greater level of angiotensin II in patients with nonpulsatile devices, which in animal research contributes substantially to background SNA. 21 Furthermore, a chronic increase in aldosterone has a similar sympathoexcitatory action, such as observed in patients with primary hyperaldosteronism in whom MSNA is markedly elevated.…”
Section: Mechanisms For Sympathetic Activation With Nonpulsatile Flowmentioning
confidence: 99%